1993
DOI: 10.1029/92jb02175
|View full text |Cite
|
Sign up to set email alerts
|

Upper mantle Q structure beneath the East Pacific Rise

Abstract: A model of Qβ as a function of depth has been determined for the upper mantle beneath the East Pacific Rise. The model is appropriate for shear waves with periods from roughly 15 to 30 s. The amplitudes of multibounce SH phases which propagate within the upper mantle were used to constrain the Q structure. The multibounce phase amplitudes were measured with respect to the S wave amplitude for each seismogram. The data consist of S, SS, SSS, and SSSS waves for distances from 30° to 80°. The sources are earthqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…In general, models obtained to date at the global scale concur with regional scale models on the existence of a correlation of lateral variations in Q with tectonic province, in the first 250 km of the upper mantle, with high Q under shields and low Q under oceans, particularly so under young oceans. Surface wave derived models (ROMANOWICZ, 1990(ROMANOWICZ, , 1995DUREK et al, 1993) tend to indicate high attenuation under young oceans (as confirmed by regional studies, e.g., DING and GRAND, 1993). ROMANOWICZ (1994b) demonstrated the correlation of Q with the age of the sea floor in the first 250 km of the upper mantle, both in the Pacific and in the Atlantic Oceans (Fig.…”
Section: Existing Global Models and Stable Featuressupporting
confidence: 59%
See 1 more Smart Citation
“…In general, models obtained to date at the global scale concur with regional scale models on the existence of a correlation of lateral variations in Q with tectonic province, in the first 250 km of the upper mantle, with high Q under shields and low Q under oceans, particularly so under young oceans. Surface wave derived models (ROMANOWICZ, 1990(ROMANOWICZ, , 1995DUREK et al, 1993) tend to indicate high attenuation under young oceans (as confirmed by regional studies, e.g., DING and GRAND, 1993). ROMANOWICZ (1994b) demonstrated the correlation of Q with the age of the sea floor in the first 250 km of the upper mantle, both in the Pacific and in the Atlantic Oceans (Fig.…”
Section: Existing Global Models and Stable Featuressupporting
confidence: 59%
“…The existence of large lateral variations of Q in the crust (see MITCHELL, 1995 for a review) and the upper mantle, is well documented from various regional studies, either using surface waves (e.g., MITCHELL, 1975;MITCHELL, 1978, 1981;NAKANISHI, 1979a;BUSSY et al, 1993) or body waves, such as multiple ScS phases (NAKANISHI, 1979b;SIPKIN and JORDAN, 1980;LAY and WALLACE, 1983;CHAN and DER, 1988;SIPKIN and REVENAUGH, 1994) or multiple S and depth phases (SHEEHAN and SOLOMON, 1992;WIENS, 1990, 1994;DING and GRAND, 1993). These lateral variations can be an order of magnitude larger than observed lateral variations in velocity, commonly exceeding 50-100%.…”
Section: Anelastic Tomography: Goals and Issuesmentioning
confidence: 99%
“…Improved data coverage and measurement techniques have led to numerous models of attenuation on both global scales (DUREK et al, 1993;ROMANOWICZ, 1995;BHATTACHARYYA et al, 1998) and regional scales (REVENAUGH and JORDAN, 1991;SHEEHAN and SOLOMON, 1992;DING and GRAND, 1993;SIPKIN and REVENAUGH, 1994;FLANAGAN and WIENS, 1994;MITCHELL, 1995). A universal feature of these models is the presence of a low-Q asthenosphere and upper mantle with lateral variations in attenuation which are quite strong.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have chosen a frequency-independent attenuation model which is equivalent to those used in similar analyses of long-period seismic data (BHAT-TACHARYYA et al, 1996, 1998DING and GRAND, 1993;FLANAGAN and WIENS, Figure 11 A comparison between time-domain (a) and frequency-domain (b) measurements for teleseismic S waveforms. We observe considerably more scatter in the time-domain measurements, probably due to biased picks.…”
Section: Frequency-domain Technique 6ersusmentioning
confidence: 99%
“…Several body-wave attenuation studies involve the analysis of long-period waveforms to constrain Q i variations in the mantle (SIPKIN and JORDAN, 1980;REVENAUGH and JORDAN, 1991;BHATTACHARYYA et al, 1996BHATTACHARYYA et al, , 1998WALLACE, 1983, 1988;CHAN and DER, 1988;SHEEHAN and SOLOMON, 1992;DING and GRAND, 1993;REID and WOODHOUSE, 1997;SIPKIN and REVENAUGH, 1994;WIENS, 1990, 1994). The attenuation of seismic body waves is typically obtained from their pulse shapes.…”
Section: Introductionmentioning
confidence: 99%